The Effect of Using Android-Based Learning Media on Student Interest and Learning Outcomes in Lessons Islamic Education - Agustiana Agustiana; Syaripudin Basyar; Agus Jatmiko (STAI Serdang Lubuk Pakam, 2022)
This study aims to determine the interest in learning, and student learning outcomes before and after the treatment is given learning media based on android applications on fardhu kifayah material, in terms of increasing student interest and learning outcomes. This research was conducted at SMK Negeri 7 Bandar Lampung by dividing into two groups, namely the experimental class and the control class. The experimental research design was carried out by collecting interest in learning questionnaire data and learning achievement tests. The collected description data will be processed using SPSS 23. The results showed that the experimental and control class students' learning interest after treatment was 87.91%. The results of the t-count calculation of 6.416 are greater than the t-table of 1.668. The experimental learning outcomes obtained an average of 79.15, while the control class was 63.27. Increased learning outcomes indicate this from before treatment (52.30 to 79.15). There is a significant difference between the control, and experimental classes, the t-count of 5.321 is greater than the t-table of 1.668. Thus the hypothesis that there is a significant influence of the media on learning interest and student learning outcomes in the use of android-based applications for fardhu kifayah is acceptable.